Spray behaviour and particulate matter emissions with M15 methanol/gasoline blends in a GDI engine - Mohd Murad, S; Camm, J; Stone, R; Davy, M; Richardson, D (Society of Automotive Engineers, 2016)
Model M15 gasoline fuels have been created from pure fuel components, to give independent control of volatility, the heavy end content and the aromatic content, in order to understand the effect of the fuel properties on Gasoline Direct Injection (GDI) fuel spray behaviour and the subsequent particulate number emissions. Each fuel was imaged at a range of fuel temperatures in a spray rig and in a motored optical engine, to cover the full range from non-flashing sprays through to flare flashing sprays. The spray axial penetration (and potential piston and liner impingement), and spray evaporation rate were extracted from the images. Firing engine tests with the fuels with the same fuel temperatures were performed and exhaust particulate number spectra captured using a DMS500 Mark II Particle Spectrometer. Data from the spray images and knowledge of the fuel evaporative performance has been used to explain some of the observed findings that might appear to be against the expected trends, but can be explained in terms of the saturation pressure ratio - the ratio of